1999
DOI: 10.1128/mcb.19.6.4324
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Repression Modules Is Critical for Heme Regulation of the Yeast Transcriptional Activator Hap1

Abstract: Heme plays key regulatory roles in numerous molecular and cellular processes for systems that sense or use oxygen. In the yeast Saccharomyces cerevisiae, oxygen sensing and heme signaling are mediated by heme activator protein 1 (Hap1). Hap1 contains seven heme-responsive motifs (HRMs): six are clustered in the heme domain, and a seventh is near the activation domain. To determine the functional role of HRMs and to define which parts of Hap1 mediate heme regulation, we carried out a systematic analysis of Hap1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 38 publications
(89 reference statements)
4
65
0
2
Order By: Relevance
“…HRMs are short sequence motifs that contain Cys residues [14,21,29,38,39] (Figure 2B). Not all of the seven HRMs are equally important for the activation of Hap1 [40,41]. Experimental evidence suggests that HRM7 is critical for heme activation of Hap1, while HRMs 1-6 appear to play auxiliary roles and are dispensable for Hap1 activation by heme [40,41].…”
Section: The Yeast Transcriptional Activator Hap1 Acts As a Key Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…HRMs are short sequence motifs that contain Cys residues [14,21,29,38,39] (Figure 2B). Not all of the seven HRMs are equally important for the activation of Hap1 [40,41]. Experimental evidence suggests that HRM7 is critical for heme activation of Hap1, while HRMs 1-6 appear to play auxiliary roles and are dispensable for Hap1 activation by heme [40,41].…”
Section: The Yeast Transcriptional Activator Hap1 Acts As a Key Mediamentioning
confidence: 99%
“…Not all of the seven HRMs are equally important for the activation of Hap1 [40,41]. Experimental evidence suggests that HRM7 is critical for heme activation of Hap1, while HRMs 1-6 appear to play auxiliary roles and are dispensable for Hap1 activation by heme [40,41]. Heme promotes Hap1 transcriptional activity by enhancing the association of Hsp90 to the Hap1-Hsp70-Ydj1-Sro9 multichaperone complex, causing conformational changes in the complex [14,29,31,34,36,37,40,41].…”
Section: The Yeast Transcriptional Activator Hap1 Acts As a Key Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA fragment containing −321 to −360 overlaps with the −341 to −380 DNA fragment and exhibited strong complex formation (lanes 19 and 20), although the percentage of bound vs. free was higher for the −341 to −380 DNA fragment. All longer DNA fragments containing the −341 to −380 region formed Hap1-dependent complexes (see lanes [7][8][9][10][11][12][13][14][15][16]. The DNA fragment containing the −380 to −461 region also formed a Hap1-dependent complex (lanes 17 and 18), but it was much weaker, compared to that formed on the −341 to −380 DNA fragment.…”
Section: The Hap1 Protein Binds Specifically To the Hap1 Promoter Seqmentioning
confidence: 99%
“…The mechanism of heme-dependent transcriptional activation by Hap1 has been well studied [4,[9][10][11]. Previous studies have shown that heme regulation of Hap1 activity requires molecular chaperones Hsp90, Hsp70 and its cochaperones Ydj1 and Sro9 [12][13][14][15][16]. Hsp70 and its cochaperones Ydj1 and Sro9 confer Hap1 repression at low heme levels, whereas Hsp90 promotes heme activation of Hap1 [12][13][14][15]17].…”
Section: Introductionmentioning
confidence: 99%